Whither the Political Science Major? Curricular Design and Program Learning Outcomes at 110 US Colleges and Universities. - Feeley, Maureen; Van Vechten, Renée (PS: Political Science & Politics, 2021)
The article presents the discussion on American Political Science Association's (APSA) last significant review of undergraduate political science education. Topics include programs providing for sequential learning; and gaining familiarity with the different assumptions, methods, and analytical approaches used by political scientists.